To the Jew first or to the Jew last? Romans 1:16c and Jewish missional priority in dialogue with Jews for Jesus - Fritz, Antoine X. J. (Cambridge : James Clarke, 2014)
Many missions to the Jewish people, such as Jews for Jesus, use Romans 1:16 as a proof text to encourage the evangelisation of the Jewish people as a priority: ""to the Jew first, and then to the Greek"" (Jewish Missional Priority). Is this interpretation of the text legitimate? After considering when this priority first appeared, the author exposes and evaluates the arguments commonly used to promote it. His thorough exegesis of Romans 1:16-17 ultimately resolves the question. He takes the opportunity to explore some possible eschatological implications developed from Romans 9-11 and the para.
Front cover; Title page; Copyright; Contents; Foreword; Acknowledgments; Abbreviations and Acronyms; Introduction; I. Wirkungsgeschichte; II. Status Quaestionis; III. Propositio; IV. Heilsgeschichte; Conclusion; Bibliography; Back cover.
Includes bibliographical references.
Description based on CIP data; item not viewed.
Master record variable field(s) change: 072
Keywords: Bible. -- Criticism, interpretation, etc; Jews in the New Testament; Jews -- Conversion to Christianity; RELIGION / Biblical Studies / New Testament; RELIGION / Biblical Studies / Paul's Letters; Bible. Romans -- Criticism, interpretation, etc; Bible. Romans I, 1-16 -- Criticism, interpretation, etc; Jews -- Conversion to Christianity; Jews in the New Testament; Electronic books